Genealogi Pemikiran Ushul Fiqh: Kajian Sejarah, Perkembangan dan Aliran-Aliran Utama - Elok Thohirotul Mahfudloh; Alik Ifadah; Muhamad Awal Ludin; Muhamad Faruq Najib; Agus Khumaedy (Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the genealogy of the development of Usul Fiqh and the emergence of various schools of thought in Usul Fiqh from the time of the Prophet Muhammad SAW to the periodization of knowledge collection. This study uses a qualitative descriptive approach with the category of literature study. Information is collected through documentation techniques from various written sources such as books, scientific articles, academic journals, and works of Usul Fiqh scholars. The data is then analyzed using content analysis techniques to find patterns of development of thought, characteristics of schools, and contributions of Usul Fiqh figures. The results show that Usul Fiqh developed gradually from simple ijtihad practices during the time of the Prophet SAW to a systematic discipline during the time of the imams of the madhhab, especially through the contribution of Imam Shafi'i in the book al-Risalah. This study also found three main schools of Usul Fiqh, namely the Mutakallimin school, the Fuqaha/Hanafiyyah school, and the Combined school. These three schools show that Usul Fiqh develops dynamically, adaptively, and is open to social developments and the needs of the community. This study is expected to serve as a reference for the development of Usul Fiqh and Islamic education.